Public Relations Strategy For Promoting The Wardah Brand (Case Study Of Irian Supermarket Medan Tembung) - Tanjung, Farah Fatimah; Nurhanifah, Nurhanifah (Lentera: Jurnal Ilmu Dakwah dan Komunikasi, 2024)
The purpose of this study is to examine the Public relations (PR) approach that the Wardah brand used to advertise its goods at the Irian Supermarket in Medan Tembung. The research methodology used was qualitative and descriptive in nature. Observation, interviews, documentation, and literature reviews from pertinent books and journals are some of the techniques used to gather data. The research results answered that Wardah's Brand Image Public Relations Strategy in promotion at Irian Supermarket Medan Tembung uses a Public Relations strategy, namely, 1) Strategy of Publicity, 2) Strategy of Persuasion, and 3) Strategy of Image. According to research, Wardah sends press releases emphasizing the benefits of its products in order to guarantee favorable publicity by using its strong ties with the local media. Furthermore, the company actively sponsors neighborhood events and activities inside the store, organizing unique discounts and events to draw in customers. Working together with prominent locals and influencers, participating in community events, and attending social gatherings all help to improve links with customers. Along with implementing a digital PR strategy, Wardah increased its online visibility through blogs, websites, and social media platforms while continuing to engage in active customer service. Wardah extensively advertises its items at Irian Supermarket Medan Tembung, building a positive Brand image and raising consumer awareness. The company focuses on in-supermarket product demonstrations, eye-catching layouts, and innovative web advertising.